KPPIM Kuala Pilah at Karnival S3K for STEM 2024 / Tuan Norhafizah Tuan Zakaria, Siti Noor Dina Ahmad and Yusrina Andu - Tuan Zakaria, Tuan Norhafizah; Ahmad, Siti Noor Dina; Andu, Yusrina (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The College of Computing, Informatics and Mathematics (KPPIM) at UiTM Negeri Sembilan Kampus Kuala Pilah participated in the Karnival S3K held on July 31st, 2024 at SMK Seri Jempol. This event, which focused on STEM, career, health, and entrepreneurship, was organised by SMK Seri Jempol. The primary aim was to expose students to STEM careers and foster critical thinking and problem-solving skills, alongside health and entrepreneurship awareness. During the event, students actively participated in mathematical exercises, science demonstrations, and career briefings. The Karnival S3K emphasized the importance of Science, Technology, Engineering, and Mathematics (STEM) education in shaping Malaysia's future talent pool. By integrating career and health briefings, the program also encouraged students to think beyond STEM, exploring potential career paths and entrepreneurial opportunities. This multidisciplinary approach aligns with Malaysia’s national goals of fostering economic competitiveness through innovation. On July 31, 2024, three representatives from the College of Computing Informatics and Mathematics, UiTM Negeri Sembilan, Kuala Pilah Campus were involved in guiding students through interactive mathematical games, STEM workshops, and career briefings. These activities not only promoted academic interest but also highlighted entrepreneurship opportunities within the STEM fields. Students were awarded prizes for completing the exercises and mind games, which further motivated participation.